2001
DOI: 10.1046/j.1365-2141.2001.02840.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of both myeloid CD11c+ and lymphoid CD11c dendritic cell subsets in cord blood

Abstract: Summary. Dendritic cells (DCs) are the most potent antigenpresenting cells described to date. In human peripheral blood, both myeloid and lymphoid subsets of DCs have been identified. In contrast, cord blood (CB) DCs have recently been described as being exclusively of the immature CD11c 2 lymphoid DC subset. Using an alternative method of enrichment, based on a negative selection system, both lymphoid (HLA-DR 1 CD123 111 CD11c 2 CD33 2 ) and myeloid (HLA-DR 11 CD123 1 CD11c 1 CD33 1 ) DCs were identified in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
1
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 28 publications
4
58
1
2
Order By: Relevance
“…In general, an increased number and proportion of pDCs was reported in CB compared to adult peripheral blood. Widely-different pDC:mDC ratios in CB have been reported by different investigators, ranging from 1:1 to 3:1 [39][40][41][42][43]. Nevertheless, since the usual pDC:mDC ratio in adults is 1:2, a consensus towards increased pDC:mDC ratio in CB is emerging from these studies.…”
Section: Cord Blood Dendritic Cellsmentioning
confidence: 83%
See 3 more Smart Citations
“…In general, an increased number and proportion of pDCs was reported in CB compared to adult peripheral blood. Widely-different pDC:mDC ratios in CB have been reported by different investigators, ranging from 1:1 to 3:1 [39][40][41][42][43]. Nevertheless, since the usual pDC:mDC ratio in adults is 1:2, a consensus towards increased pDC:mDC ratio in CB is emerging from these studies.…”
Section: Cord Blood Dendritic Cellsmentioning
confidence: 83%
“…The ability of CB-DCs to capture antigenic protein is also altered, suggesting that those cells may in fact not function properly as APCs [27]. However, this hypothesis is challenged by the fact that unfractionated CB-DCs induce strong allogeneic responses [39], suggesting a complex picture in terms of the functionality of neonatal DCs. In that regard, data obtained in babies who have been exposed in utero to viruses bring some important information.…”
Section: Cord Blood Dendritic Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the major advantages of this culture system include the use of pre-established human allogeneic stromal layers, thus overcoming the limitations of using xenogeneic and/or transformed and immortalized human stromal cell lines, this culture system's serum-free conditions, and its ability to expand CB cells along the myeloid pathway, while simultaneously generating a population expressing a marker of early lymphopoiesis, CD7 + . Since several different investigators had reported the ability to generate NK, B, DCs and T cells [10,[16][17][18][19][20][21][22]] from a CD7 + CD34 + cell population from fresh CB and BM, in the present studies, we examined whether the CD7 + CD34negative population obtained after CB expansion over MSC layers, in serum-free medium, also had lymphocytic differentiative potential. Specifically, we investigated the ability of the CD7+ population generated in our culture system to give rise to two of the major constituents of the immune system, mature NK cells and dendritic cells (DCs) that could ultimately be used in cellular immunotherapy.…”
Section: Introductionmentioning
confidence: 99%